Semiological analysis of residence advertisements in the case of Istanbul's transformation: Architectural examples of post-2000 - GÜZELCİ, HANDAN (Istanbul Kultur Univ, Atakoy Campus, Bakırkoy, Istanbul, 34156, Turkey, 2018)
Commencing by showing its impacts in the 20th century, the concept of globalization represents an event experienced all over the World in the 21st century through political, economic, sociocultural power of nations and Technologies. Underlying dynamics of the concept of globalization lead to changes and transformation cities. Change and transformation of urban areas have seen in human daily life and architectural styles. As one of the architectural typologies and special research areas, residences are of great importance within the multi-layered structure of Istanbul which is a result of changes and transformation throughout the historical process. Within the scope of the study, residential sector is considered in terms of socio-cultural and socio-economic aspects as one of the attributes of Istanbul`s transformation. When residence models in Istanbul are approached from socioeconomic perspective, concept of consumption, technology and mass culture created by globalization driven state`s ideology and production mechanisms appears. Analysis on socio-cultural values of residence models in Istanbul shows that fashions and trends which are a product of superior entities lead to degeneration of cultural values. There is a requirement for a two-point study and determining the methodology for this study in the background of visually experienced changes and transformation in Istanbul. Analysis of roles of particularly "globalization" as well as "consumption" and "media" in transformation of a home into a residence in the historical course of residential market in Istanbul based upon progress, transformation and changes forms semantic framework of the study. Objective of the study is to discuss common statements in residence advertisements consisting of post-2000 enclosed luxurious residence settlements, high-rise residences and multi-purpose urban residences as a case study around technology and media. In the study, advertisements of 25 different residence projects appeared in the media are analyzed semiologically. As a result of the analysis, a classification was made for today`s residence systems by taking emphasis in residence advertisements as a start point. Main framework of the study consists of three parts. In part one, as a result of literature review, conceptual definitions are made for basic terms used as introduction to the subject. In part two, the place of changing and transforming residential market in Turkey and particularly in its metropolis, Istanbul, throughout historical process and factors effecting thereof are stated. Final and the third part provides impacts of residence advertisements appearing in the media with thrilling pictures on new life cultures within the perfect, uncertain and volatile structure of Istanbul.
Keywords: Globalization; transformation; Istanbul; consumption; media; residence; residence advertisements; semiological scientific analysis